On the importance of a precise crystal structure for simulating gas adsorption in nanoporous materials1. Issue 29 (7th August 2015) - Lawler, Keith V.; Hulvey, Zeric; Forster, Paul M.
<x xml:space="preserve">Abstract</x> Differences between crystal structures produces substantial changes in simulated properties, underlying the importance of utilizing appropriate structural description in calculations.